Development of a health promotion program for high risk pregnancy at Phurua Hospital - Yingyongwatanakit, Jeeranan (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
Emergency deliveries among high-risk pregnant women at Phurua Hospital frequently resulted in neonatal hypoxia due to preterm births. The primary cause was delayed healthcare access attributed to pregnant women’s lack of knowledge regarding warning signs requiring immediate medical attention. To develop and evaluate the effectiveness of a health behavior promotion program for high-risk pregnant women by comparing knowledge and health behavior scores before and after program participation. This research and development (R&D) study comprised two phases. Phase 1 involved program development by a multidisciplinary team. Phase 2 employed a quasi-experimental design with 45 high-risk pregnant women receiving antenatal care at Phurua Hospital from November 15, 2023, to March 31, 2024. The program consisted of two modules based on gestational age. Data were collected using validated knowledge and self-care skill assessment questionnaires (IOC = 1.00). Statistical analysis included descriptive statistics and paired t-tests. After program participation, high-risk pregnant women demonstrated statistically significant improvements in knowledge and health behaviors across all domains. Knowledge scores increased from 13.26 (SD=3.38) to 15.67 (SD=1.96), p<0.001. All six health behavior dimensions - nutrition, physical activity, health responsibility, interpersonal relationships, stress management, and spiritual development - showed significant improvements (p<0.05 to p<0.001). Overall mean scores improved from 30.83 (SD=4.18) to 32.26 (SD=2.90), p=0.004. The health behavior promotion program effectively enhanced knowledge and health behaviors among high-risk pregnant women. Integration into routine antenatal care services is recommended to prevent emergency delivery complications and improve maternal and neonatal health outcomes.